Nanocomposite synergy for enhanced oil recovery: Macro and micro analysis of CeO2/montmorillonite nanofluids in carbonate and sandstone reservoirs - Bahraminejad, Hossein; Khaksar Manshad, Abbas; Keshavarz, Alireza; Iglauer, Stefan; Mohammad Sajadi, S. (Fuel (Guildford), 2024)
[Display omitted] •We eco-synthesized CeO2/Montmorillonite nanocomposite using Quercetin, validated via analytical chemistry.•Zeta potential analysis affirms nanofluid stability under 1000 ppm concentration.•At 500 ppm, the EDL mechanism alters wettability by counteracting disjoining pressure.•Unique wettability observed at 500 ppm due to the electrical double layer mechanism.•We analyzed interfacial tension and wettability changes using micro-visualization.•Emulsion analysis using a novel method on micro-scaled images of micromodel. Cerium (IV) oxide has shown great potential for serving as a mutually advantageous conjunction material when applied in a synergistic manner of use with other chemicals thanks to its oxygen storage capacity. Recently, many researchers have elaborated on novel synthesis methods for achieving nanocomposites (NCs) that combine inherent properties of nano-sized CeO2 with those of montmorillonite, as a low-cost base substance. CeO2/Montmorillonite nanocomposite synthesized by application of an environmentally friendly reducing and stabilizing agent. The success of the synthesis was verified by analytical techniques including Field-Emission Scanning Electron Microscopy, Thermo-Gravimetric analysis, Energy-Dispersive X-ray Spectroscopy and Mapping, X-Ray Diffraction analysis, Fourier-Transform Infrared spectroscopy. Nanofluids were prepared by dispersing the synthesized NCs, at different concentrations as aqueous colloidal solutions and then studied for investigating the nanofluid colloidal stability. Experimental studies were undertaken on the nanofluid functioning subjects of the fluid/fluid and fluid/fluid/rock interactions area in both macro and micro scales. Macro investigations of interfacial tension and wettability alteration and also micro-analysis of microfluidic injections with proper visualizations of created effects within pore structures were carried out. The results confirmed the proper synthesis of the NC and its stability in water-based nanofluids. CeO2 nano clays showed nearly 33 % optimization of the interfacial tension (IFT) (i.e., IFT decreased from the initial value of 27 to 18 mN/m at the NC concentration of 1000 ppm). However, their effect on the alteration of wettability was significant. Indeed, at the optimum concentrations, the contact angle decreased from 151° to 19.38° at the concentration of 500 ppm for carbonate lithology (87.1 % optimization) and also it decreased from 135.5° to 18.73° at the concentration of 1500 ppm for sandstone lithology (86.1 % optimization). The effect of wettability alteration for carbonate rocks was reported to be high enough for changing the wettability to a strong water-wet state while the wettability alteration for sandstone lithology was measured to be low. Both wettability alteration studies and micro visualizations validated the strong and low wettability alteration for carbonate and sandstone lithology systems. Also, the emulsion analysis was carried out on the micro-scaled images of the pores and throats with their containing fluids by a new method of color saturation investigation which showed a promising new emulsion analysis method for micro-scaled experiments.